2023
DOI: 10.1007/s41982-023-00145-z
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Trends in Material Culture Evolution—a Case Study of Gravettian Points from Lower Austria and Moravia

Andreas Maier,
Robin John,
Florian Linsel
et al.

Abstract: Identifying, analyzing, and explaining trends in the development of material culture is one of the major concerns in prehistoric archaeology. The traditional recording of data in typologies, however, is not optimal for answering the question of diachronic change because typological data capture variability poorly and are often incompatible with multivariate statistics. To overcome these problems, we present PyREnArA (Python-R-Environment for Artifact Analysis), a trait-based tool that allows for a systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Future research should address this compositional complexity. In sum, our work aligns with approaches to lithic tool shape and technological analyses that-especially if integrated with quantitative and replicable protocols-promise an understanding of material culture change beyond typological categories and traditionally named units [195][196][197][198][199].…”
Section: Discussionmentioning
confidence: 99%
“…Future research should address this compositional complexity. In sum, our work aligns with approaches to lithic tool shape and technological analyses that-especially if integrated with quantitative and replicable protocols-promise an understanding of material culture change beyond typological categories and traditionally named units [195][196][197][198][199].…”
Section: Discussionmentioning
confidence: 99%
“…Second, a k-means clustering algorithm was utilized to distinguish between the dorsal (front) and ventral (back) sides. Third, the distal (top) and proximal (bottom) orientations are determined by the relationship between the center of mass of the artifact and the location of the centroid of its bounding box (Maier et al, 2023).…”
Section: Preprocessing In Gigameshmentioning
confidence: 99%
“…Concerning the use of this approach in the study of backed tools, its potential has been demonstrated by several scholars that have pursued questions on the diffusion of specific elements through time and space and the interrelation between morphology and techniques applied during production processes [22]- [25].…”
Section: Introductionmentioning
confidence: 99%